Students' Experiences of the Interactive Lecture Method in Learning English Vocabulary: A Case Study at SMPIT Insan Madani Aceh Barat Daya - Asmaria; Nuzulul Isna (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to explore students’ experiences of the Interactive Lecture Method in learning English vocabulary at SMPIT Insan Madani, Southwest Aceh. This study employed a qualitative case study design involving 11 eighth-grade students selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using Braun and Clarke’s (2006) thematic analysis framework. The findings revealed three main themes. First, students experienced clearer explanations through interaction, faster understanding through question-and-answer activities, and reported feeling happy, enthusiastic, more confident, and less bored during learning. Second, students memorized vocabulary through repeated practice and by linking new words to the teacher’s explanations. Third, the challenges of the Interactive Lecture Method included forgetting words easily, difficulties with vocabulary, speaking, verbs, tenses, and listening, as well as low self-confidence and limited attention. This study highlights that the Interactive Lecture Method provides interactive learning experiences that support vocabulary learning while also revealing the challenges students encounter during the learning process.